1994
DOI: 10.1159/000236675
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Residues in Bee Venom Phospholipase A<sub>2</sub> Are Important for Binding to Human Monoclonal or Polyclonal Antibodies of the lgG4 Isotope

Abstract: Discontinuous antigenic sites on bee venom phospholipase A2 (PLA) have been mapped using human monoclonal antibodies or human polyclonal serum antibodies (hpAbs) of the IgG4 isotype from beekeepers or of the IgE isotype from individuals allergic to PLA. Lysine residues of PLA have been specifically modified by acetylation or acylation by treatment with citraconic anhydride of their ε-amino groups to analyze their role in antigen-antibody binding. After the modifications, the binding of PLA to the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…A human mAb against Api m 1 (BVA2) was used to characterize further the Api m [1/2] fusion protein. 16 Immunoblotting For Western blot analysis, equimolar amounts (1.5 mmol/L) of the 3 recombinant proteins, Api m 1, Api m 2, and Api m [1/2], were electrophoresed by 4% to 12% Bis-Tris polyacrylamide NuPAGE gels (Invitrogen, Basel, Switzerland) under denaturing, reducing conditions and transferred to nitrocellulose membrane (Amersham, Little Chalfont, United Kingdom). 17 The binding of IgE in pooled serum from 4 individuals allergic to BV was detected with rabbit antihuman IgE (Dako Inc, Burlingame, Calif) and developed by goat antirabbit biotin conjugated IgG antibody (Dako Inc) and streptavidin-horseradish peroxidase (Sigma Chemical Co, St Louis, Mo).…”
Section: Generation and Characterization Of Mabs Against Api Mmentioning
confidence: 99%
See 1 more Smart Citation
“…A human mAb against Api m 1 (BVA2) was used to characterize further the Api m [1/2] fusion protein. 16 Immunoblotting For Western blot analysis, equimolar amounts (1.5 mmol/L) of the 3 recombinant proteins, Api m 1, Api m 2, and Api m [1/2], were electrophoresed by 4% to 12% Bis-Tris polyacrylamide NuPAGE gels (Invitrogen, Basel, Switzerland) under denaturing, reducing conditions and transferred to nitrocellulose membrane (Amersham, Little Chalfont, United Kingdom). 17 The binding of IgE in pooled serum from 4 individuals allergic to BV was detected with rabbit antihuman IgE (Dako Inc, Burlingame, Calif) and developed by goat antirabbit biotin conjugated IgG antibody (Dako Inc) and streptavidin-horseradish peroxidase (Sigma Chemical Co, St Louis, Mo).…”
Section: Generation and Characterization Of Mabs Against Api Mmentioning
confidence: 99%
“…A human mAb against Api m 1 (BVA2) was used to characterize further the Api m [1/2] fusion protein in dot blot assays. 16 Peroxidase-conjugated rabbit antihuman IgG antibody (Dako Inc) was used as a second antibody.…”
Section: Generation and Characterization Of Mabs Against Api Mmentioning
confidence: 99%
“…Two huMabs from the heteromyelomas BVA1 and BVA2 [37], and one from the EBV–B cell line BUB1 [21]showed identical epitope specificity involving Lys 25 of PLA. By using lysine–modified and point–mutated PLA it was demonstrated that this residue is an essential constituent of a major binding site for human anti–PLA antibodies [37, 38, 39]. In ELISA, binding of both BVA1 and BVA2 to PLA was inhibited by each other and about 90% of serum anti–PLA IgG4 antibody binding could be inhibited by the huMabs.…”
Section: Specific Antigen Recognition By B Cells Influences Differenmentioning
confidence: 99%
“…To address these issues directly, we have compared the epitopes on phospholipase A 2 (PLA), the main allergen present in bee venom (Kuchler et al, 1989;Scott et al, 1990a), recognized by human monoclonal antibodies (hmAbs) (Schneider et al, 1994b) or murine monoclonal antibodies (mmAbs) (Müller et al, 1993). Two hmAbs of the IgG 4 isotype were made from lymphocytes of a nonallergic beekeeper naturally exposed to bee venom.…”
Section: Introductionmentioning
confidence: 99%
“…Two hmAbs of the IgG 4 isotype were made from lymphocytes of a nonallergic beekeeper naturally exposed to bee venom. These hmAbs were shown to be part of the polyclonal immune response of beekeepers who have been exposed for years to bee venom via bee stings (Dudler et al, 1994;Schneider et al, 1994aSchneider et al, , 1994b. ␥-Globulins from such individuals were previously shown to be protective when given to bee venom allergic individuals before exposing them to bee venom (Lessof et al, 1978;Müller et al, 1986;Bousquet et al, 1987).…”
Section: Introductionmentioning
confidence: 99%